Arid Dune Ecosystems - Breckle, Siegmar-W. (Springer, 2017)
Sand dune dynamics plays a key role in many arid deserts. This volume provides a synthesis of a specific sand dune ecosystem, the Nizzana site in the Negev Desert. Describing its climate and geophysical/geochemical properties of soils, geological history, flora and fauna, and past/present land-use patterns, it elucidates ecological and geomorphological processes and their interrelations, based on long-term monitoring, in situ experiments and satellite imagery. Particular attention is drawn to the impact of the topsoil biological crust in controlling water availability at local/regional scales. The interdisciplinary approach adopted in this case study offers a good example of a highly complex and dynamic system, which could easily be applied to other sandy ecosystems.